GAMBARAN KADAR GULA DARAH PENDERITA DIABETES MELLITUS PESERTA PROLANIS DI PUSKESMAS 1 SUMBANG KABUPATEN BANYUMAS - Melinda Melinda; Suci Khasanah; Amin Susanto (Sekolah Tinggi Pariwisata Mataram, 2022)
Prolanis is a health care system and a proactive approach that is carried out in an integrated manner involving participants, first-level health facilities (FKTP) and BPJS health. Diabetes mellitus is a metabolic disorder characterized by increased blood glucose levels (hyperglycemia) due to damage to insulin secretion and insulin action. This study aims to determine the description of blood sugar levels in patients with diabetes mellitus who participate in prolanis at Puskesmas 1 Sumbang, Banyumas Regency. Descriptive method with a retrospective approach. The sampling technique used a total sampling of 48 elderly people who took Prolanis. Data were taken using secondary data and primary data. The results showed that the blood sugar levels of people with Diabetes Mellitus showed that the average value of blood sugar levels was 143.4 mg/dl, the minimum value was 96.6 mg/dl and the maximum value was 258 mg/dl.